Expanding cities and connecting cities: appraising the effects of transport improvements - Venables, A (University of Bath, School of Management, 2016)
Transport improvements facilitate the movement of people or goods within or between cities. The economic benefits of such improvements accrue through three main mechanisms. The first is the direct cost saving to existing and new traffic as captured by standard cost benefit analysis (CBA). The second occurs if there are urbanisation economies. Direct benefits are likely to increase economic activity in affected cities, and this may be amplified by increasing returns and urbanisation economies. The third mechanism applies principally to inter-city improvements which enable cities to specialise in particular sectors or tasks. If there are city-task level economies of scale (localisation economies) this is a further source of gain. This paper develops a model in which to analyse these mechanisms. An expression is derived for the multipliers that should be applied to a conventional CBA for intra- and inter-city improvements. Gains from specialisation and consequent scale economies may be large although, since there may be multiple equilibria, a transport improvement may be a necessary but not sufficient condition for the gains to be achieved.